Optimization of the Mathematical Model of Cyclone Separation Performance Based on Response Surface Analysis - Longfei CONG; Shengyu WANG; Jiajing LUO; Changchun ZHOU (Kuangchan zonghe liyong)
This is an article in the field of mining engineering. With the increasing application of cyclone in the field of mineral processing, the influence of its operating factors on the separation performance has been paid more and more attention in the production process. At present, various researches on the separation performance of cyclone have been widely reported, but they are generally limited to the structural factors of cyclone, and do not consider the effects of operational factors (inlet pressure P, dispersion concentration Ci) and the interaction between factors on the separation performance. In order to explore the influence of cyclone operating factors on separation performance, response surface analysis was applied to design experiments to optimize the mathematical models of cyclone main diameter Dc and operating factors on cyclone classification efficiency Ef and classifier size Dm, and explore the interaction between them, which can achieve the best separation performance regulation of cyclone. Through the analysis of 17 groups of test results by design expert, the following results are obtained: classification efficiency fitting formulaandgrading granularity fitting formula. The 3D surface response analysis shows that the main diameter, inlet pressure and inlet concentration have a significant effect on the classification efficiency and particle size of Dc> Ci >P, and for the classification efficiency and particle size, the interaction between Dc and Ci and between Dc and P is relatively strong, while the interaction between Ci and P is weak.